IMPLEMENTASI ASAS KEPENTINGAN UMUM DALAM KASUS KEPAILITAN DI INDONESIA - Faujura, Rahmanisa Purnamasari (Universitas Wiralodra, 2024)
The public interest includes the interests of the Nation and the State as well as the common interests of the people by taking into account social, political, and human rights aspects on the basis of national development principles with regard to national resilience and the insight of the archipelago. This is also included in bankcrupty cases in Indonesia, as explained in Article 2 of Law Number 37 of 2004 concerning Bankcrupty and Postponement of Debt Payment Obligations which allows the prosecutor's office to file bankruptcy applications in the public interest. Based on this explanation, the author explains in this journal related to the criteria and implementation of the public interest in bankruptcy cases in Indonesia. The research method used in writing this journal is normative juridical with analytical descriptive research specifications. Based on theresults of the study, it was explained that the criteria for public interest as applicable in Indonesia are basically everything related to the interests of the state and nation. This is shown by the absence of a Limit to the law that explains how the so-called public interest is. As for bankcrupty cases, the implementation of the principle of public interest has been explicitly explained and applied in Law Number 37 of 2004 concerning Bankcrupty and Postponement of Debt Payment Obligations, Law Number 16 of 2004 concerning the Prosecutor's Office. Under both laws, public interest is applied in the authority of the prosecutor as an applicant in bankcrupty cases.